IMPACTS OF COVID-19 ON INDIVIDUALS WITH DOWN SYNDROME - da Silva Figueredo Cintra, Isabella (2022)
Down Syndrome (DS) is a genetic disease that results in the presence of an extra 21st chromosome, which is why it is commonly called trisomy 21, this chromosomal abnormality may increase the risk of certain complications or may also present abnormalities that affect the pulmonary function, airway changes in DS patients can promote viral infections, which exacerbates the impact of Covid-19 in these patients. Therefore, this study aimed to present a deeper knowledge to the reader about how Covid-19 affects individuals with Down syndrome. This is an integrative literature review, whose data collection was carried out at the base: PubMed, in the period of May 2021 by crossing the following descriptors: Covid-19 and Down Syndrome (Down Syndrome). Articles from 2020 to 2021, with full text, in English, Portuguese or Spanish, were included in this review, and those that did not address the topic were excluded. Six studies concluded that Covid-19 patients with Down Syndrome (DS) are more likely to worsen the disease, with infections and longer hospital stays. Two studies also pointed to an increased risk of death from Covid-19 compared to people without DS. A study warned that patients with this profile should be considered at high risk for severe disease progression, in this case the child (4 months) was hospitalized and required oxygen support, being discharged after 10 days of hospitalization. Through the results, it is clear that Covid-19 has a negative and comprehensive impact on individuals with Down Syndrome, so that when they become ill, the clinical repercussions on these patients are too serious.